A'ISYAH BINT AL-SYATHI DAN AL-TAFSIR AL-BAYANI LI AL-QUR'AN AL-KARIM (TELAAH METODOLOGI, ASBAB AL-NUZUL DAN ESKATOLOGI)) - Rahmah, Wahyuni Shifatur (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2023)
Context analysis plays an important role in understanding revelatory events, because the concept of "revelation" cannot be understood unless you look at the previous context. This indicates that there is a relationship between reality (as context) and the text. One cannot possibly understand by taking the text outside of reality. Therefore, asbab al-nuzul (events that occurred and accompanied the revelation of a verse of the Qur'an) is very necessary to understand a condition. But the context here is broader than asbab al-nuzul, because asbab al-nuzul becomes necessary only to see special events. This assumption about asbab al-nuzul was developed by A'isyah Bint al-Syathi'. According to him, asbab al-nuzul is nothing more than postulates surrounding the text, or external conditions of revelation. Therefore, he emphasizes the universality of meaning rather than the specificity of the condition (al-'ibratu bi'umum al-lafzi la bi specifically al-sabab). He tried to develop a "narrative text theory" that stated that verses were revealed based on specific reasons but were expressed in the form of general pronunciations, so the general pronunciation was used as a guide.